2021
DOI: 10.1021/acs.iecr.0c05438
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metal/Acid Matching Balance over Bifunctional Pd/Hβ toward Benzene Hydroalkylation

Abstract: Bifunctional Pd/Hβ catalysts with uniformly distributed palladium nanoparticles (Pd NPs) were successfully synthesized by a facile methanol-mediated weakly capping growth approach (WCGA). A series of Pd/Hβ catalysts with different metal loadings and Si/Al ratios were used for benzene hydroalkylation, and the identification of metal/acid matching balance over bifunctional Pd/Hβ toward benzene hydroalkylation performance was investigated. The obtained characterization and catalytic activity test results demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…According to the previous work, 8 beta-supported Pd with Si/Al ratio of 30 has excellent benzene HDA performance. The protonic form of the HBeta were prepared by the ion exchange method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous work, 8 beta-supported Pd with Si/Al ratio of 30 has excellent benzene HDA performance. The protonic form of the HBeta were prepared by the ion exchange method.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the high conversion and high selectivity could not be achieved simutaneously. 5,[7][8][9][10] In addition, the active metal surfaces with the face-centered cubic and hexagonal symmetry structure binds benzene too strongly to the desorption of CHE, resulting in deep hydrogenation to cyclohexane (CHA). 11 Therefore, precisely controlling the selective production of CHE by modifying the electronic and structural properties of the metallic sites and promoting its subsequent alkylation with benzene instead of further hydrogenation, is of great significance for the whole HDA process reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The benzene hydroalkylation reaction involves the hydrogenation of benzene at metal centers to generate CHE, which subsequently undergoes alkylation with benzene at acid centers for the production of CHB. , Noteworthily, when CHE is formed at the metal site, the competing reactions of deep hydrogenation and alkylation will lead to a low selectivity to a specific product; hence, the high selectivity of CHB requires proper dual-active-site synergy. Recent studies mainly focused on the construction of metal/acid center equilibrium in bifunctional catalysts. For example, it has been reported that a metal/acid equilibrium range can be achieved by adjusting the Si/Al ratios as well as metal loadings of Pd/Hβ so as to obtain the optimal acid/metal molar ratio .…”
Section: Introductionmentioning
confidence: 99%
“…10−16 Liu et al reported that Pd/Hβ exhibited excellent catalytic performance in the hydroalkylation of benzene, with 63.4% conversion of benzene and 51.7% selectivity of CHB obtained by adjusting the metal/ acid matching equilibrium. 8 They also found that using 25% Ni/SiO 2 as the catalyst afforded >99.8% conversion of biphenyl and >96.4% selectivity of CHB after eight cycles of selective hydrogenation of biphenyl to CHB. 6 The hydroalkylation of benzene is not suitable for large-scale industrial production due to the use of expensive noble metal catalysts and high production costs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are three main routes available for the synthesis of cyclohexylbenzene: (i) partial hydrogenation of biphenyl, , (ii) hydroalkylation of benzene, , and (iii) Friedel–Crafts alkylation of benzene with cyclohexene (or cyclohexanol, or halogen cyclohexane). Liu et al reported that Pd/Hβ exhibited excellent catalytic performance in the hydroalkylation of benzene, with 63.4% conversion of benzene and 51.7% selectivity of CHB obtained by adjusting the metal/acid matching equilibrium . They also found that using 25% Ni/SiO 2 as the catalyst afforded >99.8% conversion of biphenyl and >96.4% selectivity of CHB after eight cycles of selective hydrogenation of biphenyl to CHB .…”
Section: Introductionmentioning
confidence: 99%